Laminated high-reliability high-power connection terminal and manufacturing method thereof
Through laminated structure design and advanced process technology, the thermal management and reliability of high-power connection terminals are improved, the problems of insufficient heat dissipation and low reliability in the existing technology are solved, and efficient and reliable manufacturing of high-power connection terminals is achieved.
Patent Information
- Application Number
- CN202411928915.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-power connection terminals are difficult to meet the needs of long-term and stable operation in high-power application scenarios, mainly due to the simple structural design, insufficient thermal management capabilities and low manufacturing process control accuracy.
The laminated structure design is adopted, and the metal thin film is deposited through composite ceramic substrate layer and atomic layer deposition technology, electron beam lithography and deep reactive ion etching processes are formed to form micro-nano channel structures, chemical vapor deposition deposition heat dissipation materials, self-healing polymer materials and hot pressing molding processes for insulating and protective packaging.
It significantly improves transmission efficiency and thermal management capabilities, solves the problems of insufficient heat dissipation and low reliability performance in the prior art, realizes the manufacturing of high-reliability high-power connection terminals, and meets the high-performance and high-reliability needs in high-power application scenarios.
Smart Images

Figure CN119726191A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of connectors, and in particular to a laminated high-reliability high-power connection terminal and a manufacturing method thereof. Background Art
[0002] With the rapid development of modern electronic technology and power electronics technology, high-power connectors have been widely used in many fields such as electric vehicles, high-speed charging stations, industrial power systems, and renewable energy equipment. These application scenarios place extremely high demands on the power transmission capability, thermal management performance, and mechanical reliability of the connectors. For example, in electric vehicle high-speed charging systems, connectors not only need to withstand high current and high power transmission, but also need to have excellent heat dissipation capabilities and high temperature resistance to ensure safety and stability during the charging process. In addition, as electric vehicles and renewable energy equipment move toward higher power density.
[0003] Existing high-power connection terminals usually adopt a single-layer or few-layer structure and are manufactured through traditional processes such as metal welding or crimping. The structural design of these connection terminals is relatively simple, and they mainly rely on highly conductive metal materials to achieve current transmission. However, as the transmission power increases, the single-layer structure is difficult to effectively manage the heat generated, causing the terminals to be prone to overheating, thermal expansion, and material fatigue in high-power working environments, which in turn affects the stability and reliability of the connection. In addition, the process control accuracy of traditional manufacturing processes is low, and it is difficult to achieve micro-layer-level structural optimization, which limits the performance improvement of the terminals in high-density current transmission and efficient heat dissipation. These shortcomings make it difficult for existing high-power connection terminals to meet the needs of long-term stable operation in high-power application scenarios.
[0004] In view of this, there is an urgent need to improve the high-power connection terminals and manufacturing processes in the prior art to solve the technical problem of low performance during high-power transmission. Summary of the invention
[0005] The object of the present invention is to provide a laminated high-reliability high-power connection terminal and a manufacturing method thereof to solve the above technical problems.
[0006] To achieve this object, the present invention adopts the following technical solutions: A method for manufacturing a laminated high-reliability high-power connection terminal comprises the following steps: Step S1, providing a composite ceramic as a base layer, performing an active treatment on the surface of the base layer, and then depositing a layer of highly conductive metal film on the base layer using an atomic layer deposition technique to form a first current transmission layer; Step S2, coating a photosensitive material layer on the first current transport layer, using electron beam lithography technology to define the geometry of the multilayer structure through a mask, and then using a deep reactive ion etching process to selectively etch the photosensitive material layer and the first current transport layer to form a micro-nano channel structure; wherein the micro-nano channel structure includes a conductive channel for current transmission and a heat dissipation channel for thermal management; Step S3, depositing a heat dissipation material between the formed first current transmission layer and the heat dissipation channel by a chemical vapor deposition method to form a first heat dissipation layer; Step S4, repeatedly depositing heat dissipation material alternately between the heat dissipation layer and the next current transmission layer through the same deposition process, gradually constructing a multi-layer stacked structure, wherein each level of the multi-layer stacked structure includes a current transmission layer and a heat dissipation layer; Step S5, applying a self-healing polymer material at the junction of the current transmission layer and the heat dissipation layer of adjacent layers, uniformly distributing the self-healing polymer material at key connection nodes through an impregnation or coating process, and tightly combining the self-healing polymer material with the metal layer and the heat dissipation layer through a curing process; Step S6, after the deposition and integration of all current transmission layers, heat dissipation layers and self-healing materials are completed, a multi-layer insulation protection layer is packaged using a hot pressing process to obtain a laminated high-reliability high-power connection terminal.
[0007] Optionally, the step S1 specifically includes: Step S11, selecting a material for a composite ceramic substrate, wherein the material of the composite ceramic substrate is prepared by mixing aluminum oxide and silicon nitride in a ratio of 3:1; and then polishing the surface of the composite ceramic substrate using a chemical mechanical polishing process; Step S12, in a working environment, using a plasma cleaning device to perform oxygen plasma treatment on the surface of the composite ceramic substrate to form a substrate layer, the treatment time is 10 minutes, and the gas flow rate is 50 sccm; Step S13, using an atomic layer deposition device to deposit a highly conductive metal film on the surface of the substrate layer; the metal of the metal film is selected to be tungsten or copper, and the deposition thickness ranges from 50 to 100 nanometers; The deposition conditions are as follows: Deposition temperature: 250°C; number of cycles: 1000; Precursor gas: Use dichlorotungsten as a tungsten precursor, or tetramethylcopper as a copper precursor; Carrier gas: Nitrogen was used as carrier gas with a flow rate of 100 sccm; Pulse time: The precursor pulse time is 0.1 seconds, and the carrier gas purge time is 10 seconds.
[0008] Optionally, after step S13, the following steps are further included: Step S14, after the metal deposition is completed, the metal film is heat treated by an annealing process to form a first current transport layer, the annealing temperature is set to 400° C., and the duration is 30 minutes; Step S15, depositing a thin protective film on the surface of the first current transport layer, using silicon nitride or fluorinated polymer, with a thickness of 20 nanometers by chemical vapor deposition.
[0009] Optionally, the step S2 specifically includes: Step S21, on the surface of the first current transport layer, a layer of photosensitive material is evenly coated by spin coating, with a coating thickness of 500 nanometers; the spin coating parameters are set to a rotation speed of 3000 rpm and a rotation time of 30 seconds; Step S22, placing the substrate coated with the photosensitive material layer in an electron beam lithography device, performing pattern exposure using electron beam lithography technology, and using a multi-layer mask design to define a geometric pattern of the multi-layer structure, wherein the geometric pattern includes a micro-nano pattern of a current transmission path and a heat dissipation channel; Step S23, after the pattern exposure is completed, a developer is used to perform a development process, the development time is set to 60 seconds, and the temperature is 20°C to reveal the defined micro-nano pattern; after development, a soft baking process is used, the temperature is set to 120°C, and the duration is 90 seconds to further fix the micro-nano pattern.
[0010] Optionally, after step S23, the following steps are further included: Step S24, placing the developed substrate in a deep reactive ion etching system to perform selective etching to remove the metal film portion not protected by the photosensitive material; The etching process parameters are set as follows: Etching gas combination: a mixture of carbon fluoride and argon (Ar) in a ratio of 1:5; The etching power was set to 200 W, the reactive gas flow rate was 50 sccm, and the etching rate was controlled at 100 nm / min; Step S25, using scanning electronic equipment to perform morphology detection on the formed micro-nano channel structure, and by analyzing the flatness and roughness of the channel surface, obtain performance parameters of the micro-nano channel structure to optimize and adjust the set electron beam lithography parameters and etching process parameters.
[0011] Optionally, the step S3 specifically includes: Step S31, selecting any one of graphene, silicon nitride or silicon carbide composite materials as a heat dissipation material, and performing pre-treatment on the selected heat dissipation material, wherein the pre-treatment includes chemical cleaning and drying; Step S32, setting the CVD process parameters of the CVD reactor, wherein the CVD process parameters include deposition temperature, pressure, gas flow rate and deposition time, as follows: Deposition temperature: 1200°C; deposition pressure: 5 Torr; reaction gas flow rate: a mixed gas of ammonia and methane with a flow ratio of 1:2, and the flow rates were set to 100 sccm and 200 sccm respectively; deposition time: 60 minutes; Step S33, placing the formed micro-nano channel structure substrate into a CVD reactor, starting the CVD reactor, and depositing the heat dissipation material according to the set CVD process parameters to form a first heat dissipation layer; Step S34, after the deposition is completed, the CVD reactor is closed and slowly cooled to room temperature, and the surface morphology of the first heat dissipation layer is detected using scanning electronic equipment to detect the film uniformity and surface defects of the first heat dissipation layer.
[0012] Optionally, the step S5 specifically includes: Step S51, selecting a polymer based on dynamic covalent bonds as a polymer matrix, adding a thermally conductive filler to the polymer matrix, uniformly mixing the polymer matrix and the thermally conductive filler in a solvent, and treating with an ultrasonic disperser for 30 minutes to uniformly disperse the thermally conductive filler in the polymer matrix to form a self-healing polymer solution; wherein the thermally conductive filler may be aluminum oxide nanoparticles or carbon nanotubes; Step S52, cleaning the interface between the current transmission layer and the heat dissipation layer of the adjacent layers, using anhydrous ethanol or acetone for cleaning, and then using plasma treatment to activate the cleaned surface, and the plasma activation parameters are set as follows: Gas type: oxygen; Power: 100 W; Processing time: 5 minutes; Gas flow rate: 50 sccm; Step S53, slowly immersing the activated multi-layer stacked structure into a self-healing polymer solution for 2 minutes, so that the self-healing polymer composite material fully penetrates into the micropores and gaps at the key connection nodes; Or use a coating process: use dispensing equipment to evenly coat the self-healing polymer solution at key connection nodes; Step S54, placing the coated or impregnated multilayer stacked structure in a curing furnace for curing treatment, and setting the temperature program of the curing process: heating to 60°C and keeping for 1 hour; then heating to 120°C and keeping for 2 hours; slowly cooling to room temperature, with a cooling rate of 1°C / min.
[0013] Step S55, hot pressing is performed between the self-healing polymer material and the metal layer and the heat dissipation layer to strengthen the interlayer bonding; the hot pressing conditions are as follows: Hot pressing temperature: 100°C; Pressure: 0.5 MPa; Time: 30 minutes Step S56, sampling the multi-layer stacked structure after the solidification and strengthening treatment, and performing a self-healing performance test.
[0014] Optionally, the process of the self-healing performance test is: Step S561, using a cutter to make a scratch of a preset depth on the self-healing polymer layer; Step S562, placing the sample in a room temperature environment, observing the healing of the scratch, and recording the healing time; Step S563, using electronic scanning equipment to compare and analyze the surface morphology before and after healing; Step S564, performing mechanical property testing to evaluate the tensile strength and elongation at break of the sample before and after self-healing.
[0015] Optionally, the step S6 specifically includes: Step S61, selecting and preparing an insulating protective layer material and a ceramic filler layer; the insulating protective layer material is selected from any one of polyimide, polyethylene terephthalate or liquid crystal polymer film; Step S62, stacking and preforming the multi-layer insulation protection layer material; the specific process of stacking is: first cutting the insulation protection layer material into insulation material sheets matching the preset size, and then alternately stacking with the ceramic filler layer, and forming a multi-layer structure in the order of insulation material sheet ceramic filler layer / insulation material sheet, and the number of layers is set to 3 to 5 layers; the specific process of preforming is: using a vacuum laminator to pre-press the stacked structure, the pre-pressing conditions are temperature 80°C, pressure 0.1MPa, time 5 minutes, to obtain a multi-layer insulation protection layer preform with preliminary bonding force; Step S63, aligning and positioning the multi-layer insulation protection layer preform with the multi-layer stacked structure having all current transmission layers, heat dissipation layers and self-healing materials; Step S64, placing the aligned and positioned overall structure in a hot pressing molding machine to perform a hot pressing molding process; setting hot pressing process parameters: heating stage, heating from room temperature to 150°C, with a heating rate of 5°C / minute; keeping stage, keeping at 150°C for 30 minutes; pressurizing condition: pre-pressing at 0.2 MPa for 5 minutes, then gradually increasing the pressure to 1 MPa, and keeping the pressure constant; cooling stage, slowly cooling to room temperature, with a cooling rate of 2°C / minute; Step S65, taking out the packaged laminated structure from the hot pressing machine, inspecting the appearance, trimming the edges, and polishing the package surface; Step S66, conduct a dielectric strength test, use a high voltage breakdown test, gradually increase the test voltage from 0 V to 5 kV, record the breakdown voltage, and determine whether the dielectric strength of the insulation layer meets the standard to obtain a qualified laminated high-reliability high-power connection terminal.
[0016] The present invention further provides a laminated high-reliability high-power connection terminal, which is manufactured by the manufacturing method of the laminated high-reliability high-power connection terminal as described above, and the laminated high-reliability high-power connection terminal specifically comprises: A substrate layer, the surface of which is activated and a layer of highly conductive metal film is deposited thereon to form a first current transport layer; A micro-nano channel structure, located on the first current transport layer, the micro-nano channel structure comprising a conductive channel for current transport and a heat dissipation channel for thermal management; A first heat dissipation layer is disposed between the first current transmission layer and the heat dissipation channel, and the first heat dissipation layer is formed by depositing a heat dissipation material by a chemical vapor deposition method; A multi-layer stack structure including a plurality of stacked current transmission layers and heat dissipation layers alternating with each other; A self-healing polymer material layer located at the interface between the current transmission layer and the heat dissipation layer at adjacent levels; The multi-layer insulating protective layer is encapsulated outside the laminated structure that completes all current transmission layers, heat dissipation layers and self-healing materials. The multi-layer insulating protective layer is formed by a hot pressing molding process to provide insulation and protection for the laminated structure.
[0017] Compared with the prior art, the present invention has the following beneficial effects: during processing, by selecting a composite ceramic substrate and performing a surface active treatment, subsequent metal film deposition is ensured to form a first current transmission layer; by using electron beam lithography and deep reactive ion etching processes, a micro-nano channel structure is accurately formed on the metal layer, which is used for current transmission and heat dissipation management respectively; by chemical vapor deposition, a heat dissipation material is deposited between the current transmission layer and the heat dissipation channel to improve the thermal management capability; the deposition process is repeated to gradually construct a multi-layer stacked structure, each layer of which includes a current transmission layer and a heat dissipation layer, thereby enhancing the overall power transmission and heat dissipation effect; self-healing polymer materials are introduced at key connection nodes of adjacent levels, and an automatic repair function is realized by an impregnation or coating process to improve the mechanical stability and reliability of the connection terminal; then, the entire multi-layer structure is insulated and protected by a hot pressing process; the method significantly improves the transmission efficiency and thermal management capability through the application of a multi-layer stacked structure and advanced materials, solves the problems of insufficient heat dissipation and low reliability performance in the prior art, realizes the manufacture of high-reliability and high-power connection terminals of the stack, and meets the requirements for high performance and high reliability of the connection terminals in high-power application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.
[0020] Figure 1 This is a schematic diagram of a process of manufacturing a laminated high-reliability high-power connection terminal according to the first embodiment; Figure 2 The second schematic flow chart of the method for manufacturing the laminated high-reliability high-power connection terminal of the first embodiment; Figure 3 The third schematic diagram is a flow chart of the method for manufacturing the laminated high-reliability high-power connection terminal of the first embodiment. DETAILED DESCRIPTION
[0021] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the description of the present invention, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.
[0023] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0024] Embodiment 1: Combination Figures 1 to 3 As shown, an embodiment of the present invention provides a method for manufacturing a laminated high-reliability high-power connection terminal, comprising the following steps: Step S1, providing a composite ceramic as a base layer, performing an active treatment on the surface of the base layer, and then using an atomic layer deposition technique to deposit a layer of a highly conductive metal film on the base layer to form a first current transmission layer.
[0025] Step S2, coating a layer of photosensitive material on the first current transport layer, using electron beam lithography technology to define the geometry of the multilayer structure through a mask, and then using a deep reactive ion etching process to selectively etch the photosensitive material layer and the first current transport layer to form a micro-nano channel structure; wherein the micro-nano channel structure includes a conductive channel for current transmission and a heat dissipation channel for thermal management.
[0026] Step S3, depositing heat dissipation material between the formed first current transmission layer and the heat dissipation channel by chemical vapor deposition to form a first heat dissipation layer.
[0027] Step S4, through the same deposition process, repeatedly depositing the heat dissipation material alternately between the heat dissipation layer and the next current transmission layer, gradually constructing a multi-layer stacking structure, each level of the multi-layer stacking structure includes a current transmission layer and a heat dissipation layer.
[0028] Step S5, applying the self-healing polymer material at the junction of the current transmission layer and the heat dissipation layer of adjacent layers, uniformly distributing the self-healing polymer material at the key connection nodes through an impregnation or coating process, and tightly combining the self-healing polymer material with the metal layer and the heat dissipation layer through a curing process.
[0029] Step S6, after the deposition and integration of all current transmission layers, heat dissipation layers and self-healing materials are completed, a multi-layer insulation protection layer is packaged using a hot pressing process to obtain a laminated high-reliability high-power connection terminal.
[0030] The working principle of the present invention is as follows: during processing, a composite ceramic substrate is selected and surface active treatment is performed to ensure subsequent metal film deposition to form a first current transmission layer; electron beam lithography and deep reactive ion etching processes are used to accurately form a micro-nano channel structure on the metal layer, which is used for current transmission and heat dissipation management respectively; heat dissipation materials are deposited between the current transmission layer and the heat dissipation channel by chemical vapor deposition to improve thermal management capabilities; the deposition process is repeated to gradually build a multi-layer stacked structure, each layer of which includes a current transmission layer and a heat dissipation layer, thereby enhancing the overall power transmission and heat dissipation effects; self-healing polymer materials are introduced at key connection nodes of adjacent levels, and automatic repair functions are realized by impregnation or coating processes to improve the mechanical stability and reliability of the connection terminal; then the entire multi-layer structure is insulated and protected by a hot pressing process; the method significantly improves the transmission efficiency and thermal management capabilities through the application of multi-layer stacking structures and advanced materials, solves the problems of insufficient heat dissipation and low reliability performance in the prior art, realizes the manufacture of high-reliability and high-power connection terminals of the stacked layers, and meets the requirements for high performance and high reliability of the connection terminals in high-power application scenarios.
[0031] In this embodiment, it is specifically explained that step S1 specifically includes: Step S11, selecting a material for a composite ceramic substrate, the material of the composite ceramic substrate is prepared by mixing aluminum oxide and silicon nitride in a ratio of 3:1; it has excellent thermal conductivity (≥150 W / m·K) and electrical insulation performance (dielectric constant ≤3.5). Then, a chemical mechanical polishing process is used to polish the surface of the composite ceramic substrate; the surface roughness Ra ≤0.5 nanometers is achieved to ensure uniform deposition of the metal film in subsequent processes.
[0032] Step S12, in a working environment, a plasma cleaning device is used to perform oxygen plasma treatment on the surface of the composite ceramic substrate to form a substrate layer, the treatment time is 10 minutes, and the gas flow rate is 50 sccm; to enhance the chemical activity of the substrate surface and the adhesion of the metal film. After the treatment, a scanning electron microscope (SEM) is used to perform morphological analysis on the substrate surface to ensure that the surface activity treatment achieves the expected effect.
[0033] Step S13, using an atomic layer deposition device to deposit a highly conductive metal film on the surface of the substrate layer; the metal of the metal film is selected to be tungsten or copper, and the deposition thickness ranges from 50 to 100 nanometers; wherein the deposition conditions are as follows: Deposition temperature: 250°C; number of cycles: 1000 times; to ensure uniformity and density of the film; Precursor gas: Use dichlorotungsten as a tungsten precursor, or tetramethylcopper as a copper precursor; Carrier gas: Nitrogen was used as carrier gas with a flow rate of 100 sccm; Pulse time: The precursor pulse time is 0.1 seconds, and the carrier gas purge time is 10 seconds.
[0034] Through atomic layer deposition technology, the metal film is ensured to have high uniformity and excellent conductive properties, with a resistivity of ≤1.5 μΩ·cm.
[0035] Step S14: After the metal deposition is completed, the metal film is heat treated by annealing process to form the first current transmission layer. The annealing temperature is set to 400°C and the duration is 30 minutes to improve the crystal structure and conductive properties of the metal film. After annealing, the crystal structure and composition of the metal film are analyzed using X-ray diffraction (XRD) and energy dispersive spectrum analysis (EDS) to ensure the purity of the film and the uniformity of the grain size.
[0036] Step S15, depositing a thin protective film on the surface of the first current transport layer, using silicon nitride or fluorinated polymer, with a thickness of 20 nanometers by chemical vapor deposition, to prevent oxidation and contamination in subsequent processes and improve the durability of the current transport layer.
[0037] In this embodiment, it is specifically described that step S2 specifically includes: Step S21, a layer of photosensitive material (such as electron beam photoresist) is evenly coated on the surface of the first current transport layer by spin coating, with a coating thickness of 500 nanometers; the spin coating parameters are set to a rotation speed of 3000 rpm and a rotation time of 30 seconds to ensure the uniformity and thickness consistency of the photosensitive material layer. After coating, a soft baking process is performed in a clean room environment, with a temperature set to 90°C and a duration of 60 seconds to remove the solvent and enhance the adhesion of the photosensitive material.
[0038] Step S22, placing the substrate coated with the photosensitive material layer in an electron beam lithography device, using electron beam lithography technology to perform pattern exposure, using a multi-layer mask design to define the geometry of the multi-layer structure, the geometry including the micro-nano pattern of the current transmission path and the heat dissipation channel; wherein the graphic design of each layer uses a different mask alignment to achieve a complex multi-layer superimposed structure.
[0039] The electron beam lithography parameters were set to an acceleration voltage of 100 kV, an electron beam dose of 200 μC / cm², and a beam spot size controlled within 10 nanometers to ensure high resolution and accuracy of the graphics.
[0040] Step S23, after the pattern exposure is completed, a developer is used for development treatment, the development time is set to 60 seconds, the temperature is 20°C, to reveal the defined micro-nano pattern; after development, a soft baking process is used, the temperature is set to 120°C, the duration is 90 seconds, to further fix the micro-nano pattern.
[0041] Step S24, placing the developed substrate in a deep reactive ion etching system to perform selective etching to remove the metal film portion not protected by the photosensitive material; The etching process parameters are set as follows: Etching gas combination: a mixture of carbon fluoride and argon (Ar) in a ratio of 1:5; The etching power was set to 200 W, the reactive gas flow rate was 50 sccm, and the etching rate was controlled at 100 nm / min; The etching depth reaches 100 nanometers to form a micro-nano channel structure with depth and width that meet the design requirements. After etching, a plasma cleaning process is used to remove the residual photosensitive material to ensure the cleanliness and precision of the micro-nano channel structure.
[0042] Step S25, using scanning electronic equipment to perform morphology detection on the formed micro-nano channel structure, and by analyzing the flatness and roughness of the channel surface, obtain performance parameters of the micro-nano channel structure to optimize and adjust the set electron beam lithography parameters and etching process parameters.
[0043] Atomic force microscopy (AFM) is used to further analyze the flatness and roughness of the channel surface to ensure the high precision and consistency of the micro-nano channel. Based on the test results, the electron beam lithography and etching process parameters are adjusted to optimize the formation process of the micro-nano channel structure to achieve the dual functions of the current transmission path and the heat dissipation channel required by the design.
[0044] In this embodiment, it is specifically described that step S3 specifically includes: Step S31, selecting any one of graphene, silicon nitride or silicon carbide composite materials as a heat dissipation material, and performing pre-treatment on the selected heat dissipation material, wherein the pre-treatment includes chemical cleaning and drying; Pre-treatment of the selected heat dissipation material, including chemical cleaning and drying, removes surface impurities and moisture, and ensures that the material purity reaches more than 99.99% to prevent defects from being introduced during the deposition process. According to the required heat dissipation effect, adjust the ratio and particle size distribution of the heat dissipation material to optimize the material performance.
[0045] Step S32, setting the CVD process parameters of the CVD reactor, the CVD process parameters including deposition temperature, pressure, gas flow rate and deposition time, are as follows: Deposition temperature: 1200°C; to ensure good crystallization and high thermal conductivity of the material; deposition pressure: 5 Torr; to optimize the gas phase reaction rate and film density; reaction gas flow: a mixed gas with a flow ratio of 1:2 of ammonia and methane, with flow rates set to 100 sccm and 200 sccm respectively; to control the composition and structure of the material. Deposition time: 60 minutes; to ensure uniform deposition of the desired thickness.
[0046] Step S33, placing the formed micro-nano channel structure substrate into a CVD reactor, starting the CVD reactor, and depositing the heat dissipation material according to the set CVD process parameters to form a first heat dissipation layer; during the deposition process, the film thickness and deposition rate are monitored in real time to ensure the uniformity and density of the material.
[0047] During the deposition process, a rotating substrate stage is used to enhance the uniformity of gas distribution and avoid uneven film thickness. Plasma-assisted CVD (PECVD) technology is introduced to use plasma to excite the reaction gas, increase the deposition rate and film quality, and further improve the crystallinity and thermal conductivity of the heat dissipation material.
[0048] Step S34, after the deposition is completed, the CVD reactor is closed and slowly cooled to room temperature, and the surface morphology of the first heat dissipation layer is detected using scanning electronic equipment to detect the film uniformity and surface defects of the first heat dissipation layer.
[0049] X-ray diffraction (XRD) is used to analyze the crystal structure of the deposited layer to ensure that the phase purity and grain size of the material meet the design requirements. Raman spectroscopy is used to verify the quality and uniformity of the graphene layer to ensure its high thermal conductivity.
[0050] Subsequent treatment and protection of the first heat dissipation layer: A thin protective film, such as silicon nitride (SiN x ) or fluorinated polymers to prevent oxidation and contamination in subsequent processes.
[0051] The plasma enhanced CVD (PECVD) method is used to deposit a protective film with a thickness of 30 nanometers to ensure the stability and durability of the heat dissipation material.
[0052] The thickness and composition of the protective film are accurately measured by transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS) to ensure that it meets the design specifications.
[0053] In this embodiment, it is specifically described that step S5 specifically includes: Step S51, selecting a polymer based on dynamic covalent bonds as a polymer matrix, adding a thermally conductive filler to the polymer matrix, mixing the polymer matrix and the thermally conductive filler evenly in a solvent, and treating with an ultrasonic disperser for 30 minutes to evenly disperse the thermally conductive filler in the polymer matrix to form a self-healing polymer solution; wherein the thermally conductive filler can be aluminum oxide nanoparticles or carbon nanotubes.
[0054] In order to improve the thermal conductivity and mechanical strength of the material, a thermally conductive filler can be added to the self-healing polymer. The thermally conductive filler can be aluminum oxide (Al2O3) nanoparticles or carbon nanotubes, and the filler addition amount is 5%-10% of the polymer mass.
[0055] The polymer material and the filler are uniformly mixed in a solvent, and an ultrasonic disperser is used for 30 minutes to ensure that the filler is uniformly dispersed in the polymer matrix to form a self-healing polymer composite material solution.
[0056] Step S52, cleaning the interface between the current transmission layer and the heat dissipation layer of the adjacent layers, using anhydrous ethanol or acetone for cleaning, and then using plasma treatment to activate the cleaned surface, and the plasma activation parameters are set as follows: Gas type: oxygen; Power: 100 W; Processing time: 5 minutes; Gas flow rate: 50 sccm.
[0057] Surface activation treatment can improve the interface bonding force between the self-healing polymer material and the metal layer and the heat dissipation layer.
[0058] Step S53, slowly immersing the activated multi-layer stacked structure into a self-healing polymer solution for 2 minutes, so that the self-healing polymer composite material fully penetrates into the micropores and gaps at the key connection nodes; Or adopt coating process: use dispensing equipment to evenly apply self-healing polymer solution on key connection nodes.
[0059] The dispensing needle diameter was 100 μm and the dispensing speed was 5 mm / s. To ensure uniform distribution of the self-healing polymer material, spin coating was performed with a spin speed of 500 rpm for 60 seconds.
[0060] Step S54, placing the coated or impregnated multilayer stacked structure in a curing furnace for curing treatment, and setting the temperature program of the curing process: heating to 60°C and keeping for 1 hour; then heating to 120°C and keeping for 2 hours; slowly cooling to room temperature, with a cooling rate of 1°C / min.
[0061] During the curing process, it can be carried out under the protection of an inert gas (such as nitrogen) with a gas flow rate of 100 sccm to prevent oxidation and contamination.
[0062] Step S55, hot pressing is performed between the self-healing polymer material and the metal layer and the heat dissipation layer to strengthen the interlayer bonding; the hot pressing conditions are as follows: Hot pressing temperature: 100°C; Pressure: 0.5 MPa; Duration: 30 minutes.
[0063] During the hot pressing process, a vacuum environment is used with a pressure lower than 10⁻³Torr to avoid bubble formation and improve the interface bonding quality.
[0064] Step S56, sampling the multi-layer stacked structure after the solidification and strengthening treatment, and performing a self-healing performance test.
[0065] In this embodiment, the process of the self-healing performance test is specifically described as follows: Step S561 , using a cutter to make scratches with a preset depth (about 50 microns) on the self-healing polymer layer.
[0066] Step S562, placing the sample in a room temperature environment, observing the healing of the scratch, and recording the healing time.
[0067] Step S563, using electronic scanning equipment to compare and analyze the surface morphology before and after healing.
[0068] Step S564, performing mechanical property testing to evaluate the tensile strength and elongation at break of the sample before and after self-healing.
[0069] The self-healing performance test was followed by a thermal cycle test, which cycled 100 times between -40°C and 150°C to evaluate the thermal stability and bonding strength of the interface between the self-healing polymer material and the metal layer and the heat dissipation layer.
[0070] Electrical performance tests were conducted to measure the contact resistance of the terminals to ensure that the introduction of the self-healing polymer material did not affect the current transmission performance.
[0071] In this embodiment, it is specifically described that step S6 specifically includes: Step S61, selecting and preparing an insulating protective layer material and a ceramic filler layer; the insulating protective layer material is selected from any one of polyimide, polyethylene terephthalate or liquid crystal polymer film.
[0072] These materials are insulating materials with high dielectric strength and high temperature resistance, such as polyimide (PI), polyethylene terephthalate (PET) or liquid crystal polymer (LCP) films; to enhance the insulation performance and mechanical strength, ceramic filler layers such as aluminum oxide (Al2O3) or boron nitride (BN) nanosheets are added between the insulating materials, and the thickness of the filler layer is controlled at 10 to 20 microns.
[0073] Step S62, stacking and preforming the multi-layer insulating protective layer material; the specific process of stacking is: first cut the insulating protective layer material into insulating material sheets matching the preset size, and then alternately stack them with the ceramic filler layer to form a multi-layer structure in the order of insulating material sheet ceramic filler layer / insulating material sheet, and the number of layers is set to 3 to 5 layers; the specific process of preforming is: use a vacuum laminator to pre-press the stacked structure, the pre-pressing conditions are temperature 80°C, pressure 0.1 MPa, time 5 minutes, to obtain a multi-layer insulating protective layer preform with preliminary bonding force.
[0074] Step S63, aligning and positioning the multi-layer insulating protective layer preform with the multi-layer stacked structure having all current transmission layers, heat dissipation layers and self-healing materials.
[0075] Use high-precision alignment equipment to ensure that the multi-layer insulation protection layer is accurately aligned with the edges and key parts of the multi-layer structure, with a positioning accuracy of ±10 microns; apply a thin adhesive with a thickness of no more than 5 microns, such as epoxy resin glue or modified phenolic resin, between the multi-layer insulation protection layer and the multi-layer structure to ensure a tight bond at the interface.
[0076] Step S64, placing the aligned and positioned overall structure in a hot pressing molding machine for hot pressing molding process; setting hot pressing process parameters: heating stage, heating from room temperature to 150°C, with a heating rate of 5°C / minute; keeping stage, keeping at 150°C for 30 minutes to ensure that the adhesive is fully cured and the multi-layer insulating protective layer is tightly combined with the multi-layer structure; pressurization conditions are to pre-press at 0.2 MPa for 5 minutes, and then gradually increase the pressure to 1 MPa to keep the pressure constant; cooling stage, slowly cooling to room temperature, with a cooling rate of 2°C / minute; during the hot pressing process, keep the vacuum degree below 10⁻³Torr to prevent bubbles from being generated and ensure the packaging quality.
[0077] Step S65, taking out the packaged laminated structure from the hot pressing machine, inspecting the appearance, trimming the edges, and polishing the package surface.
[0078] Check the appearance to ensure there are no defects such as blistering, delamination or cracks; use precision cutting equipment to trim the edges of the package structure and remove excess insulating material to make its size and shape meet the design requirements; polish the package surface with fine sandpaper or polishing cloth for 2 minutes to make the surface smooth and flat, and improve the environmental resistance of the insulating layer.
[0079] Step S66, conduct a dielectric strength test, use a high voltage breakdown test, gradually increase the test voltage from 0 V to 5 kV, record the breakdown voltage, and determine whether the dielectric strength of the insulation layer meets the standard to obtain a qualified laminated high-reliability high-power connection terminal.
[0080] Use an insulation resistance tester to measure the insulation resistance of the insulation layer. It is required that under standard environmental conditions, the insulation resistance should not be less than 10 9 Ω; conduct thermal cycle test, cycle 100 times at -55°C to 125°C to evaluate the thermal stability and reliability of the package structure; use X-ray non-destructive testing equipment to check the internal structure of the package to ensure that there are no gaps and defects between the layers.
[0081] Laser engraving is performed on the surface of the packaged connection terminals to mark the model, batch and production date. The engraving depth is 10 microns, which does not affect the performance of the insulation layer. Final performance testing is carried out, including electrical performance, mechanical performance and environmental adaptability testing, to ensure that the product meets the design and standard requirements. Qualified products are cleaned and the surface is wiped with a dust-free cloth to remove dust and fingerprints to ensure the cleanliness of the product. The product is packaged in anti-static and moisture-proof packaging bags, and a qualified label is affixed, ready for warehousing or shipment.
[0082] Embodiment 2: The present invention further provides a laminated high-reliability high-power connection terminal, which is manufactured by the manufacturing method of the laminated high-reliability high-power connection terminal as in the first embodiment. The laminated high-reliability high-power connection terminal specifically comprises: The substrate layer has a surface that is activated and has a layer of highly conductive metal film deposited thereon to form a first current transport layer.
[0083] The micro-nano channel structure is located on the first current transmission layer, and the micro-nano channel structure includes a conductive channel for current transmission and a heat dissipation channel for heat management.
[0084] The first heat dissipation layer is arranged between the first current transmission layer and the heat dissipation channel, and is formed by depositing heat dissipation material by a chemical vapor deposition method.
[0085] The multi-layer stacked structure includes multiple superimposed current transfer layers and heat dissipation layers alternating with each other; the current transfer layers and the heat dissipation layers are constructed by repeated deposition processes, and each level includes a current transfer layer and a heat dissipation layer.
[0086] The self-healing polymer material layer is located at the junction of the current transmission layer and the heat dissipation layer of adjacent layers; the self-healing polymer material is evenly distributed at the key connection nodes through a dipping or coating process, and is tightly combined with the metal layer and the heat dissipation layer through a curing process.
[0087] The multi-layer insulating protective layer is encapsulated outside the laminated structure that completes all current transmission layers, heat dissipation layers and self-healing materials. The multi-layer insulating protective layer is formed by a hot pressing molding process to provide insulation and protection for the laminated structure.
[0088] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for manufacturing a laminated high-reliability high-power connection terminal, characterized in that: The following steps are involved: Step S1, providing a composite ceramic as a base layer, performing an active treatment on the surface of the base layer, and then depositing a layer of highly conductive metal film on the base layer using an atomic layer deposition technique to form a first current transmission layer; Step S2, coating a photosensitive material layer on the first current transport layer, using electron beam lithography technology to define the geometry of the multilayer structure through a mask, and then using a deep reactive ion etching process to selectively etch the photosensitive material layer and the first current transport layer to form a micro-nano channel structure; wherein the micro-nano channel structure includes a conductive channel for current transmission and a heat dissipation channel for thermal management; Step S3, depositing a heat dissipation material between the formed first current transmission layer and the heat dissipation channel by a chemical vapor deposition method to form a first heat dissipation layer; Step S4, repeatedly depositing heat dissipation material alternately between the heat dissipation layer and the next current transmission layer through the same deposition process, gradually constructing a multi-layer stacked structure, wherein each level of the multi-layer stacked structure includes a current transmission layer and a heat dissipation layer; Step S5, applying a self-healing polymer material at the junction of the current transmission layer and the heat dissipation layer of adjacent layers, uniformly distributing the self-healing polymer material at key connection nodes through an impregnation or coating process, and tightly combining the self-healing polymer material with the metal layer and the heat dissipation layer through a curing process; Step S6, after the deposition and integration of all current transmission layers, heat dissipation layers and self-healing materials are completed, a multi-layer insulation protection layer is packaged using a hot pressing process to obtain a laminated high-reliability high-power connection terminal.
2. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 1, characterized in that: The step S1 specifically includes: Step S11, selecting a material for a composite ceramic substrate, wherein the material for the composite ceramic substrate is prepared by mixing aluminum oxide and silicon nitride in a ratio of 3:1; and then polishing the surface of the composite ceramic substrate using a chemical mechanical polishing process; Step S12, in a working environment, using a plasma cleaning device to perform oxygen plasma treatment on the surface of the composite ceramic substrate to form a substrate layer, the treatment time is 10 minutes, and the gas flow rate is 50 sccm; Step S13, using an atomic layer deposition device to deposit a highly conductive metal film on the surface of the substrate layer; the metal of the metal film is selected to be tungsten or copper, and the deposition thickness ranges from 50 to 100 nanometers; The deposition conditions are as follows: Deposition temperature: 250°C; number of cycles: 1000; Precursor gas: Use dichlorotungsten as a tungsten precursor, or tetramethylcopper as a copper precursor; Carrier gas: Nitrogen was used as carrier gas with a flow rate of 100 sccm; Pulse time: The precursor pulse time is 0.1 seconds, and the carrier gas purge time is 10 seconds.
3. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 2, characterized in that: After step S13, the following steps are also included: Step S14, after the metal deposition is completed, the metal film is heat treated by an annealing process to form a first current transport layer, the annealing temperature is set to 400° C., and the duration is 30 minutes; Step S15, depositing a thin protective film on the surface of the first current transport layer, using silicon nitride or fluorinated polymer, with a thickness of 20 nanometers by chemical vapor deposition.
4. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 1, characterized in that: The step S2 specifically includes: Step S21, on the surface of the first current transport layer, a layer of photosensitive material is evenly coated by spin coating, with a coating thickness of 500 nanometers; the spin coating parameters are set to a rotation speed of 3000 rpm and a rotation time of 30 seconds; Step S22, placing the substrate coated with the photosensitive material layer in an electron beam lithography device, performing pattern exposure using electron beam lithography technology, and using a multi-layer mask design to define a geometric pattern of the multi-layer structure, wherein the geometric pattern includes a micro-nano pattern of a current transmission path and a heat dissipation channel; Step S23, after the pattern exposure is completed, a developer is used to perform a development process, the development time is set to 60 seconds, and the temperature is 20°C to reveal the defined micro-nano pattern; after development, a soft baking process is used, the temperature is set to 120°C, and the duration is 90 seconds to further fix the micro-nano pattern.
5. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 4, characterized in that: After step S23, the following steps are also included: Step S24, placing the developed substrate in a deep reactive ion etching system to perform selective etching to remove the metal film portion not protected by the photosensitive material; The etching process parameters are set as follows: Etching gas combination: a mixture of carbon fluoride and argon (Ar) in a ratio of 1:5; The etching power was set to 200 W, the reactive gas flow rate was 50 sccm, and the etching rate was controlled at 100 nm / min; Step S25, using scanning electronic equipment to perform morphology detection on the formed micro-nano channel structure, and by analyzing the flatness and roughness of the channel surface, obtain performance parameters of the micro-nano channel structure to optimize and adjust the set electron beam lithography parameters and etching process parameters.
6. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 1, characterized in that: The step S3 specifically includes: Step S31, selecting any one of graphene, silicon nitride or silicon carbide composite materials as a heat dissipation material, and performing pre-treatment on the selected heat dissipation material, wherein the pre-treatment includes chemical cleaning and drying; Step S32, setting the CVD process parameters of the CVD reactor, wherein the CVD process parameters include deposition temperature, pressure, gas flow rate and deposition time, as follows: Deposition temperature: 1200°C; deposition pressure: 5 Torr; reaction gas flow rate: a mixed gas of ammonia and methane with a flow ratio of 1:2, and the flow rates were set to 100 sccm and 200 sccm respectively; deposition time: 60 minutes; Step S33, placing the formed micro-nano channel structure substrate into a CVD reactor, starting the CVD reactor, and depositing the heat dissipation material according to the set CVD process parameters to form a first heat dissipation layer; Step S34, after the deposition is completed, the CVD reactor is closed and slowly cooled to room temperature, and the surface morphology of the first heat dissipation layer is detected using scanning electronic equipment to detect the film uniformity and surface defects of the first heat dissipation layer.
7. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 1, characterized in that: The step S5 specifically includes: Step S51, selecting a polymer based on dynamic covalent bonds as a polymer matrix, adding a thermally conductive filler to the polymer matrix, uniformly mixing the polymer matrix and the thermally conductive filler in a solvent, and treating with an ultrasonic disperser for 30 minutes to uniformly disperse the thermally conductive filler in the polymer matrix to form a self-healing polymer solution; wherein the thermally conductive filler may be aluminum oxide nanoparticles or carbon nanotubes; Step S52, cleaning the interface between the current transmission layer and the heat dissipation layer of the adjacent layers, using anhydrous ethanol or acetone for cleaning, and then using plasma treatment to activate the cleaned surface, and the plasma activation parameters are set as follows: Gas type: oxygen; Power: 100 W; Processing time: 5 minutes; Gas flow rate: 50 sccm; Step S53, slowly immersing the activated multi-layer stacked structure into a self-healing polymer solution for 2 minutes, so that the self-healing polymer composite material fully penetrates into the micropores and gaps at the key connection nodes; Or use a coating process: use dispensing equipment to evenly coat the self-healing polymer solution at key connection nodes; Step S54, placing the coated or impregnated multilayer stacked structure in a curing furnace for curing treatment, and setting the temperature program of the curing process: heating to 60°C and keeping for 1 hour; then heating to 120°C and keeping for 2 hours; slowly cooling to room temperature, with a cooling rate of 1°C / min. Step S55, hot pressing is performed between the self-healing polymer material and the metal layer and the heat dissipation layer to strengthen the interlayer bonding; the hot pressing conditions are as follows: Hot pressing temperature: 100°C; Pressure: 0.5 MPa; Time: 30 minutes Step S56, sampling the multi-layer stacked structure after the solidification and strengthening treatment, and performing a self-healing performance test.
8. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 7, characterized in that: The process of the self-healing performance test is: Step S561, using a cutter to make a scratch of a preset depth on the self-healing polymer layer; Step S562, placing the sample in a room temperature environment, observing the healing of the scratch, and recording the healing time; Step S563, using electronic scanning equipment to compare and analyze the surface morphology before and after healing; Step S564, performing mechanical property testing to evaluate the tensile strength and elongation at break of the sample before and after self-healing.
9. The method for manufacturing a laminated high-reliability high-power connection terminal according to claim 1, characterized in that: The step S6 specifically includes: Step S61, selecting and preparing an insulating protective layer material and a ceramic filler layer; the insulating protective layer material is selected from any one of polyimide, polyethylene terephthalate or liquid crystal polymer film; Step S62, stacking and preforming the multi-layer insulating protective layer material; the specific process of stacking is: first cutting the insulating protective layer material into insulating material sheets matching the preset size, and then alternately stacking with the ceramic filler layer, and forming a multi-layer structure in the order of insulating material sheet ceramic filler layer / insulating material sheet, and the number of layers is set to 3 to 5 layers; the specific process of preforming is: using a vacuum laminator to pre-press the stacked structure, the pre-pressing conditions are temperature 80°C, pressure 0.1 MPa, time 5 minutes, to obtain a multi-layer insulating protective layer preform with preliminary bonding force; Step S63, aligning and positioning the multi-layer insulation protection layer preform with the multi-layer stacked structure having all current transmission layers, heat dissipation layers and self-healing materials; Step S64, placing the aligned and positioned overall structure in a hot pressing molding machine to perform a hot pressing molding process; setting hot pressing process parameters: heating stage, heating from room temperature to 150°C, with a heating rate of 5°C / minute; keeping stage, keeping at 150°C for 30 minutes; pressurizing condition: pre-pressing at 0.2 MPa for 5 minutes, then gradually increasing the pressure to 1 MPa, and keeping the pressure constant; cooling stage, slowly cooling to room temperature, with a cooling rate of 2°C / minute; Step S65, taking out the packaged laminated structure from the hot pressing machine, inspecting the appearance, trimming the edges, and polishing the package surface; Step S66, conduct a dielectric strength test, use a high voltage breakdown test, gradually increase the test voltage from 0 V to 5 kV, record the breakdown voltage, and determine whether the dielectric strength of the insulation layer meets the standard to obtain a qualified laminated high-reliability high-power connection terminal.
10. A laminated high-reliability high-power connection terminal, characterized in that: The method for manufacturing a laminated high-reliability high-power connection terminal according to any one of claims 1 to 9 is used, and the laminated high-reliability high-power connection terminal specifically comprises: A substrate layer, the surface of which is activated and a layer of highly conductive metal film is deposited thereon to form a first current transport layer; A micro-nano channel structure, located on the first current transport layer, the micro-nano channel structure comprising a conductive channel for current transport and a heat dissipation channel for thermal management; A first heat dissipation layer is disposed between the first current transmission layer and the heat dissipation channel, and the first heat dissipation layer is formed by depositing a heat dissipation material by a chemical vapor deposition method; A multi-layer stack structure including a plurality of stacked current transmission layers and heat dissipation layers alternating with each other; A self-healing polymer material layer located at the interface between the current transmission layer and the heat dissipation layer at adjacent levels; The multi-layer insulating protective layer is encapsulated outside the laminated structure that completes all current transmission layers, heat dissipation layers and self-healing materials. The multi-layer insulating protective layer is formed by a hot pressing molding process to provide insulation and protection for the laminated structure.
Citation Information
Cited By
Press-fit preparation method of high-thermal-conductivity circuit board and high-thermal-conductivity circuit board
CN120018396A
Intelligent sensor semiconductor wafer preparation method based on vapor deposition
CN120864805A